OPTIMALISASI PERAN LEMBAGA DESA DALAM MENINGKATKAN PARTISIPASI PEMBANGUNAN DI DESA (Universitas Wijayakusuma Purwokerto, 2024)
Synergy and participation are the main things that need to receive primary attention in efforts to realize development in society, especially in villages. In an effort to realize sustainable development, the development aspect is not only aimed at today's society but also at future society. Therefore, it is hoped that with participation between elements in society, development in the village can run more optimally. This service activity is aimed at empowering village institutions so that they can play their role in actively participating in the synergy of implementing development in the village. This activity was carried out in July 2024 in Pliken Village, Kembaran District, Banyumas Regency. The main target of this activity is village institutional officials in Pliken Village. This activity is carried out offline through a socialization mechanism during the routine village government meeting agenda. The results of the activity show that there has been an increase in understanding and insight into the importance of synergy and participation between village institutions to optimize village development programs.